Geopolis - Tsiganes, Europeens sans frontières
A documentary film about the Roma population in the world, with a special emphasis on Roma communities in Central-Eastern Europe. The documentary traces their origins and documents their nomadic life combining old archival footage with contemporary images. Interviews and comments of experts, scholars, local leaders and Roma with various occupations are included in the documentary. Appearances of: Marcel Courthiades (Professor of Romany language, France), Bela Danyi (Auschwitz survivor), Günter Grass (Nobel-Prize winning German author), Henriette Asseo (Historian, France), Ion Mihai Pletos (Gypsy Baron, Romania), Paul Iulian (Mayor of Vidra, Romania), Francisc Giurgiu (Mayor of Livezi, Romania), Grigore Voroneanu (Mayor of Gulia, Romania), Erika Csovcsics (High School Director, Hungary), George Soros (businessman, philanthropist and CEU Founder), Dimitrina Petrova (Executive Director of the European Roma Rights Center in Budapest, Hungary), Aladar Kotai (leader of the Gypsy Minority and President of the Roma Council in Ozd, Hungary), and Angéla Kóczé (Sociologist, Hungary).